ANALISIS PENDAPATAN USAHATANI KAKAO DI DESA MASEBEWA KECAMATAN PAGA KABUPATEN SIKKA - Gabriel Otan Apelabi; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
This research was conducted in Masebewa Village, Paga District, Sikka Regency, in December 2022. The objective of this study was to determine the amount of income and the relative profit obtained by cocoa farmers. The results showed that the cropping pattern applied by the respondent farmers was a mixed cropping pattern, in which cocoa plants were cultivated together with other crops such as cloves, coconut, candlenut, jackfruit, and vanilla. The average production of cocoa farming obtained by the respondent farmers consisted of 507.11 kg of dried cocoa beans and 397 kg of semi-dried cocoa beans in one production cycle. To carry out the farming activities, farmers incurred an average total cost of IDR 320,270.27 and obtained a total revenue of IDR 9,332,432.43. Thus, the total profit obtained by the respondent farmers in one production cycle was IDR 9,012,162.16. These results indicate that cocoa farming provides a significant contribution to supporting the income and welfare of farmers and their families in Masebewa Village.